If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + 2x = 3(2 + x) 3 + 2x = (2 * 3 + x * 3) 3 + 2x = (6 + 3x) Solving 3 + 2x = 6 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 3 + 2x + -3x = 6 + 3x + -3x Combine like terms: 2x + -3x = -1x 3 + -1x = 6 + 3x + -3x Combine like terms: 3x + -3x = 0 3 + -1x = 6 + 0 3 + -1x = 6 Add '-3' to each side of the equation. 3 + -3 + -1x = 6 + -3 Combine like terms: 3 + -3 = 0 0 + -1x = 6 + -3 -1x = 6 + -3 Combine like terms: 6 + -3 = 3 -1x = 3 Divide each side by '-1'. x = -3 Simplifying x = -3
| 7*(18+4)-13= | | 9+5x-3x=27 | | 4n+n+4=16-(n) | | 3x+4=-32 | | -6x-30= | | -6x+10=-56 | | 12x^2y^2+29x^2y= | | 4n+n+4=16-n | | 2(6y+3z-1)=12y+3z-1 | | 3x+70-7x= | | x-(8)=-2 | | 4x-8x=-24 | | 4x/7-4=12 | | 8n-4=12 | | x-(9)=-7 | | 12c-6=10c+4 | | 3a+11=4a+8 | | 4/5x+3=5x | | 4g-9=(-3g)+12 | | 2/3(3x+12)=32 | | 3(x+5)+4=3x+4 | | .2x^2+16x=0 | | 42=-6(-2x-3) | | 5(2x+3)-2=-2(x+4) | | 6(7x+3)=354 | | -3/7x+4 | | M/2=m-2/3 | | 4(-2x-5)=-76 | | 3p=9p-12 | | (15,625a^-18b^3c^24)^1/6 | | x^3-5x+12=0 | | x^3+5x-12=0 |